Postpartum anal incontinence - A. L. Petrushin; A. V. Pryalukhina (Акушерство, гинекология и репродукция, 2019)
Postpartum anal incontinence is a complex disorder that develops mainly in young women and negatively affects their social and professional activity. The aim of this review is to summarize the available literature and current concepts on the etiology, pathogenesis, diagnosis and treatment of postpartum anal incontinence. The prevalence of postpartum anal incontinence varies from 13 to 39 %. The risk factors include vaginal delivery, the use of instrumental methods, age, body mass index > 30, delivery-associated perineal tears, incontinence during pregnancy and smoking. The role of episiotomy in anal incontinence is not clear, some authors note a high risk of median episiotomy compared with mid-lateral one. Diagnosis of anal incontinence is mainly based on clinical examination and history data. The most informative imaging modality is endoanal ultrasound. Treatment of anal incontinence should begin with diet correction and medications for stool control. The efficacy of various treatment programs directed to strengthening the pelvic floor and anal sphincter muscles is controversial and needs further study. Surgical treatment is indicated if the conservative therapy is unsuccessful; the most common methods are sphincteroplasty and electroneuromodulation of the sacral plexus branches. Primary prevention measures for postpartum anal incontinence should focus on eliminating or reducing the risk factors. Special training programs for obstetricians can significantly reduce the number of perineal tears and their severity, as well as reduce the need in obstetric forceps. Secondary prevention steps include the correct choice of the first and subsequent deliveries in women with an increased risk.